Impact of Agropastoral Management on Wind Erosion in Sahelian Croplands. (29th September 2017) - Pierre, Caroline; Kergoat, Laurent; Hiernaux, Pierre; Baron, Christian; Bergametti, Gilles; Rajot, Jean‐Louis; Abdourhamane Toure, Amadou; Okin, Gregory S.; Marticorena, Beatrice
Abstract: In the Sahel, climate change and demographic growth are raising major concerns about the ability of crop yields to support the local population. Agropastoral management affects wind erosion (e.g., through crop residue management and tillage practices, which modify surface characteristics), which itself substantially affects soil fertility and thus crop yields. There is therefore a need to assess the potential impact of the main Sahelian cropping practices – like sowing, manuring, and crop residue management – on wind erosion. Using a modeling approach adapted to an experimental site located in southwestern Niger over the period 2006–2012, and scenarios that describe a set of agropastoral practices, the impacts of these practices on wind erosion are simulated and compared. The results indicate that horizontal fluxes differ by a factor of 10 among scenarios, with annual horizontal fluxes ranging from 121 to 1, 317 kg m −1 . Modeled wind erosion is most sensitive to the mass of crop residues in the late dry season, but different practices dealing with crop growth or with crop residue management may result in fluxes of the similar magnitude. The collection of the crop residues after grain harvest increases wind erosion, whereas grazing might have mixed effects, probably further mediated by the mobility of livestock as a response to forage availability. The seasonal dynamics of the monthly cumulated horizontal fluxes vary depending on practice; however, the annual cumulated horizontal fluxes are closely correlated with meteorological conditions such as wind speed and rainfall in the previous year. Copyright © 2017 John Wiley & Sons, Ltd.